Clinical and pathological features of anti‐neutrophil cytoplasmic antibody‐associated vasculitis in patients with minor urinary abnormalities. Issue 11 (25th October 2018) - Hasegawa, Jumpei; Hoshino, Junichi; Sekine, Akinari; Hayami, Noriko; Suwabe, Tatsuya; Sumida, Keiichi; Mise, Koki; Ueno, Toshiharu; Yamanouchi, Masayuki; Hazue, Ryo; Sawa, Naoki; Ohashi, Kenichi; et al.
Abstract: Aim: Kidney biopsy is the gold standard for diagnosis of anti‐neutrophil cytoplasmic antibody (ANCA)‐associated vasculitis (AAV), but it is unknown whether vasculitis can be detected from AAV patients with minor urinary abnormalities. Methods: Ninety ANCA‐positive patients undergoing kidney biopsy were evaluated retrospectively after being divided into two groups, which were group A (minor urinary abnormalities with both proteinuria <0.5 g/day and red blood cells ≤5/high power field) and group B (major urinary abnormalities except group A). Results: Thirteen patients were included in group A and 77 patients were in group B. Crescentic glomeruli were detected less frequently in group A than in group B (61.5% vs. 92.2%, P  < 0.01). The percentage of crescentic glomeruli relative to total glomeruli was significantly lower in group A than in group B (median [interquartile range]; 2.7% [0–5.2%] vs. 27.3% [8.1–56.1%], P  < 0.01). Vasculitis of the small renal arteries was detected more frequently in group A than in group B without significant difference (30.8% vs. 19.5%, P  = 0.46). Overall renal vasculitis (crescentic glomeruli and/or small renal artery vasculitis) was detected less frequently in group A than in group B (69.2% vs. 92.2%, P  = 0.03). Conclusions: These findings indicate that renal biopsy can be a useful tool for histological diagnosis of ANCA‐associated vasculitis in ANCA‐positive patients with minor urinary abnormalities, even though the rate of renal vasculitis to the total number of glomeruli sampled is lower in patients with minor urinary abnormalities than patients with major abnormalities. Summary at a Glance: Kidney biopsy is the gold standard for diagnosis of AAV, but it is unknown for those with minor urinary abnormalities. We found that kidney biopsy can detect their histological vasculitis in 69.2% of AAV patients with minor urinary abnormalities.